Pediatric palliative care in neonates: a cross-sectional study from a high-complexity hospital in Latin America. Neopalped study - Molina-Gómez, Karen; Cuervo-Suárez, María Isabel; Henao, Kevin Mauricio; Gómez, Inés Elvira; Proaño, Catalina; Duque, Natalia; Jaramillo, Martha Lucia; Marmolejo, Mariana; Burbano, Laura Sofía; García-Quintero, Ximena (BMC palliative care)
Background Pediatric palliative care (PPC) aims to alleviate suffering, improve quality of life, and facilitate decision-making for patients, families, and healthcare professionals. Specifically, PPC in neonatal patients influences their quality of life by considering the fragility and complexity of their diagnoses when performing clinical interventions. However, to date, data on newborn patients and their specialized palliative care needs is limited. Therefore, this study aims to describe the clinical characteristics of neonatal patients requiring pediatric palliative care in a specialized center of health in a low- and middle-income country in Latin America. Methods We conducted a cross-sectional study. Neonatal patients with at least 40 weeks of corrected gestational age were included. A review of medical records was conducted to obtain information about clinical outcomes and medical management. A descriptive statistical analysis was performed considering the sociodemographic and clinical characteristics of the patients. The therapeutic strategies implemented were described, comparing deceased and surviving patients using the Chi2 test, Mann-Whitney U test, or Fisher’s Exact test. Results 263 individuals were included, of which 55.13% ( n = 145) were males. The median gestational age was 35 weeks (IQR 28–38), and the median birth weight was 1,119 g (IQR 610–1760). The most frequent diagnosis was trisomy 21 in 30% ( n = 79), followed by severe congenital heart disease in 25.5% ( n = 67). The median length of hospitalization was 25 days (IQR 8–53), adherence to the established palliative care plan was 99.6% ( n = 262), and 58% ( n = 152) of patients required weekly follow-up by pediatric palliative care. Additionally, 81.37% ( n = 214) received social work support, and 94.68% received spiritual support. Regarding clinical outcomes, 140 patients died. Among these, respiratory distress ( n = 135, 96.42%) and seizures ( n = 87, 54.37%) were the most frequent symptoms in the last 24 h of life. Deceased patients had a higher NEOMOD score and lower gestational age, which were statistically significant compared to surviving patients. Conclusions The implementation of a palliative care program in a neonatal unit facilitates multidisciplinary care that provides comfort to patients with life-limiting conditions and supports their families. Our findings highlight the importance of strengthening advanced care planning both prenatal and postnatal, being essent